1996
DOI: 10.1046/j.1537-2995.1996.36896374374.x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of soluble biologic response modifiers (complement and chemokines) by a bedside white cell‐reduction filter

Abstract: The third-generation bedside filter used in this study reliably reduced the level of white cell contamination to 4 log10 white cells per PC. It also lowered the levels of interleukin 8, RANTES, and C3a. The filter did not, however, remove (scavenge) the proinflammatory cytokines interleukin 1 beta and 6. The mechanism of chemokine and C3a removal by the filter is unknown, but it may be related to ionic interactions between these biologic response modifiers and the filter medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 40 publications
3
18
1
Order By: Relevance
“…Moreover, it has been shown that some biofilter materials can absorb complement split products as well as other inflammatory mediators, e.g. cytokines [8, 25], and we have recently demonstrated that polysulfone absorbs serum factors that have a leucocyte-activating effect [26]. However, the levels of C3a measured in our study are within the range found in predialysis serum samples, analysed by the same technique, from uremic patients [27], making the clinical impact of C3a in our platelet concentrates ambiguous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been shown that some biofilter materials can absorb complement split products as well as other inflammatory mediators, e.g. cytokines [8, 25], and we have recently demonstrated that polysulfone absorbs serum factors that have a leucocyte-activating effect [26]. However, the levels of C3a measured in our study are within the range found in predialysis serum samples, analysed by the same technique, from uremic patients [27], making the clinical impact of C3a in our platelet concentrates ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been proposed that post-storage filtration can remove biologically active products generated during storage (e.g. C3a) [8]. …”
Section: Introductionmentioning
confidence: 99%
“…In non-leucocyte-reduced platelets, whether prepared from whole blood, by the buffy-coat method, or by apheresis, there is progressive accumulation of CXCL4, CXCL7, CCL5 and CXCL8 [68][69][70][71][72][73]. CXCL8 can reach particularly high levels in non-leucoreduced platelets by the end of the storage period.…”
Section: Accumulation Of Chemokines During Blood Component Storagementioning
confidence: 99%
“…CXCL8 can reach particularly high levels in non-leucoreduced platelets by the end of the storage period. Pre-storage leucocyte reduction can prevent the accumulation of leucocyte-derived CXCL8, but not platelet-derived chemokines [68,69,71,[73][74][75][76]. Photochemical pathogen reduction treatment or ultraviolet B irradiation prevents accumulation of leucocyte-derived chemokines, but γ -irradiation does not [70,77,78].…”
Section: Accumulation Of Chemokines During Blood Component Storagementioning
confidence: 99%
See 1 more Smart Citation